Clinical Progress of PD-1/L1 Inhibitors in Breast Cancer Immunotherapy - Chen, Fei; Chen, Naifei; Gao, Yangyang; Jia, Lin; Lyu, Zheng; Cui, Jiuwei (Frontiers in Oncology, 2022)
Breast cancer is a major killer of women's health worldwide. While breast cancer is thought to have lower immunogenicity compared to other solid tumors, combination therapy is able to improve the immunogenicity of the tumor and sensitize breast cancer cells to immunotherapy. Immunotherapy represented by immune checkpoint inhibitors (ICIs) has been largely explored in the field of breast cancer, including both early and advanced disease. Immunotherapy for triple-negative breast cancer (TNBC) has been the most studied, and the PD-L1 inhibitor atezolizumab combined with nab-paclitaxel has been used in the first-line treatment of TNBC. Immunotherapeutic data for human epidermal growth factor receptor positive and hormone receptor positive breast cancer are also accumulating. This review summarizes the clinical trial data of ICIs or ICIs-containing therapies in different types and stages of breast cancer.